Work environment and nurses' perspectives on missed nursing care: A scoping review - Nurhidayati, Nurhidayati; Haryanto, Haryanto; Suriadi, Suriadi (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Missed nursing care (MNC) is a global problem in nursing practice that impacts patient safety, quality of health care, and nurse job satisfaction. The nurse work environment has been identified as a key organizational factor influencing the accuracy of MNC. Purpose: To comprehensively analyse the relationship between the work environment and the incidence of missed nursing care in nurses based on publications from 2020-2025. Method: Methods of writing articles using a systematic scoping review approach, with article searches through the PubMed, ScienceDirect, Elsevier, and Google Scholar databases. The articles included are quantitative research and reviews relevant to the topic of the work environment and missed nursing care. Results: Most of the articles showed that an unfavourable work environment, such as understaffing, high workload, and low managerial support, was significantly associated with increased incidence of missed nursing care. Conclusion: The work environment plays a crucial role in missed nursing care. Improving the work environment is recommended as a primary strategy to improve the quality of nursing care and patient safety. Keyword: Missed Nursing Care; Nurses; Work Environment.